Strong convergence theorems for a class of split feasibility problems and fixed point problem in Hilbert spaces - Zhu, Jinhua; Tang, Jinfang; Chang, Shih-sen (Journal of inequalities and applications, 2018)
In this paper we consider a class of split feasibility problem by focusing on the solution sets of two important problems in the setting of Hilbert spaces. One of them is the set of zero points of the sum of two monotone operators and the other is the set of fixed points of mappings. By using the modified forward–backward splitting method, we propose a viscosity iterative algorithm. Under suitable conditions, some strong convergence theorems of the sequence generated by the algorithm to a common solution of the problem are proved. At the end of the paper, some applications and the constructed algorithm are also discussed.